Programmed death-ligand 1 and survival in colorectal cancers: A meta-analysis. Issue 4 (December 2019) - Cao, Huihua; Wang, Qing; Gao, Zhenyan; Yu, Zhan; Wu, Yugang; Lu, Qicheng
Background: Programmed death-ligand 1 (PD-L1) is a programmed death 1 (PD-1) ligand that plays a pivotal role in the inhibition of the T-cell-mediated immune response. The expression of PD-L1 is associated with the prognosis and clinical outcomes of multiple tumors. However, the prognostic value of PD-L1 overexpression in colorectal cancer is still controversial. In this study, we sought to clarify this by presenting a meta-analysis of relevant studies. Methods: Databases including PubMed, Web of Science, and EMBASE were systematically searched for studies concerning the expression of PD-L1 and survival in colorectal cancer. The reported hazard ratios (HR) with 95% confidence intervals (CI) of overall survival, disease-free survival, and recurrence-free survival in the included studies were analyzed by fixed effects/random effects models. Results: Fifteen studies involving 3078 patients with colorectal cancer were included in our meta-analysis. Overexpression of PD-L1 was found to be associated with poor overall survival (HR 1.83; 95% CI 1.21, 2.79; P = 0.005) and poor recurrence-free survival (HR 2.78; 95% CI 1.43, 5.42; P = 0.003). However, no correlation was found between PD-L1 overexpression and poor disease-free survival (HR 1.23; 95% CI 0.83, 1.82; P = 0.305). Overexpression of PD-L1 indicating poor survival held true across different geographical areas, sample sizes, analysis types, sources of HRs, and cell types. Conclusion: Overexpression of PD-L1 is associated with worse prognosis in patients with colorectal cancer and can guide physicians in the application of PD-1/PD-L1 immune checkpoint-targeted therapy.